ANALYSIS OF THE CONSTRUCTION OF THE CAR TRAILER FRAME IN TERMS OF CHANGING THE ASSEMBLY TECHNOLOGY - Jacek CABAN; Aleksander NIEOCZYM; Jonas MATIJOŠIUS; Artūras KILIKEVIČIUS; Kazimierz DROZD (Scientific Journal of Silesian University of Technology. Series Transport)
Car trailers are quite a popular means of transport and are offered in many versions, from single axle light trailers with a maximum permissible weight of 750 kg, through two- or more-axle specialized trailers. The issues of research car trailers focus on two directions: testing the driving properties and analysing the strength of the supporting frame system. Issues related to the construction of light trailers are often common to trailers used in agriculture or general transport. In this article, based on a mass-produced car trailer, an analysis was carried out regarding the choice in the technology of making the supporting structure consisting of a lower frame and an upper frame. The term upper frame should be understood as the structure on which the lifted load box rests. The costs of materials, assembly and technological possibilities of small-scale production were taken into account. In addition, strength analyses of the numerical models were carried out for critical areas of the frame during operation. After considering the unit costs for each of the analysed assembly technologies, it was shown that riveting would be the cheapest. However, the most suitable method of assembly is welding, as it allows the use of standard profiles.